2019
DOI: 10.31031/gmr.2019.03.000551
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in a Patient with Active Systemic Lupus Erythematosous Treated with Transplant of Intestinal Microbiota

Abstract: We analyzed a single case of a patient with active Systemic Lupus Erythematosus (SLE), transplanted with Intestinal Microbiota (IMT). She had 34 years old, with active SLE with 9 years of evolution. She has lupic glomerulonephritis and the last 6 months diarrhea, the she loss weight (28kg) and had desnutrition (BCI 16). Treated with racecadotrilo and loperamide. A coprologic study showed Blastocystis hominis. She did not received treatment for this parasite. An IMT was done 9 months ago, reducing diarrhea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For humans, an FMT has been performed on one 34-year-old Mexican woman suffering from SLE with glomerulonephritis, weight loss and malnutrition. An improvement has been observed with reduced diarrhoea and anxiety 102…”
Section: Challenges In the Treatment Of Slementioning
confidence: 93%
“…For humans, an FMT has been performed on one 34-year-old Mexican woman suffering from SLE with glomerulonephritis, weight loss and malnutrition. An improvement has been observed with reduced diarrhoea and anxiety 102…”
Section: Challenges In the Treatment Of Slementioning
confidence: 93%
“…The study also showed that untreated mice could be transplanted with the fecal microbiota of prednisone-treated mice without fear of side effects [127] . Clinical trials of FMT have already been conducted in patients with other autoimmune diseases, such as type 1 diabetes and ulcerative colitis, with some success [128][129] . FMT was applied to a patient with SLE who was infected with a Blastocystis hominis parasite and who also had glomerulonephritis, malnutrition, diarrhea, and severe weight loss; after FMT treatment, there was an improvement in diarrhea and anxiety [130] .…”
Section: Gut Microbiota Therapeutic Approachesmentioning
confidence: 99%